Analysis of Islamic Economic Law on Fishing Pool Business in Indonesia - Siti Nur Asia; Muthoifin; Muhamad Subhi Apriantoro; Amrin Amrin; Sya'roni Sya'roni; Rozi Irfan Rosyadi (Demak Universal Journal of Islam and Sharia, 2023)
The fishing pool business opportunity is very wide open to get big and fast profits. This study aims to reveal analytically related to Islamic law contracts in the fishing business. The research methodology uses a qualitative descriptive analysis method with a historical juridical approach. The sequence of the research process starts with collecting data on several fishing businesses. The fishing business that has been collected is then recorded and economic activities are carried out in the fishing business. Furthermore, the results of existing economic activity data are analyzed by Islamic economic law. The results of the study concluded that, there are economic activities in the fishing business that is by Islamic economic law contracts such as buying and selling and leasing (al-ijarah). In the fishing business, all buying and selling contracts are carried out by the pillars of Islamic Shari'ah related to buying and selling as long as it does not resemble gambling where ma'kud 'alaih comes from other people. Likewise, with the al-ijarah contract in the fishing business, the al-ijarah system in the fishing business has fulfilled the pillars of Islamic sharia related to al-ijarah, namely some people have a contract (subject), consent qobul, and ujrah. The activities of al-ijarah in the fishing business also have ma'jur which is ijarah In the al-ijarah fishing effort, everything is carried out by the pillars of Shari'ah law as long as it does not resemble gambling where the ma'jur comes from other people. ma'kud 'alaih comes from other people. Likewise, with the al-ijarah contract in the fishing business, the al-ijarah system in the fishing business has fulfilled the pillars of Islamic sharia related to al-ijarah, namely some people have a contract (subject), consent qobul, and ujrah. The activities of al-ijarah in the fishing business also have ma'jur which is ijarah In the al-ijarah fishing effort, everything is carried out by the pillars of Shari'ah law as long as it does not resemble gambling where the ma'jur comes from other people.